2020
DOI: 10.3906/tar-1905-87
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium carboxymethyl cellulose (Na-CMC) added to urea-formaldehyde resin on particleboard properties

Abstract: This study investigated the effect of sodium carboxymethyl cellulose (Na-CMC) added to urea-formaldehyde (UF) resin on particleboard production and its effects on the properties of the boards. The Na-CMC/UF was prepared at the selected blending levels of 0/100, 5/95, 10/90, 15/85, 20/80, 25/75, 30/70, 35/65, 40/60, 45/55, and 50/50. In the production of test panels, 55% coniferous and 45% broadleaved wood chips were used. The physical and mechanical properties of the particleboard panels were determined and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The calculated density values of the produced bark particleboards showed a maximum deviation of 5% for both board densities (320 and 420 kg/m 3 ), and the density values were within the tolerance limits specified by TS EN 312. Istek and Siradag (2013) stated that the density of particleboards is influenced by various factors, including raw material and adhesive type, as well as production conditions. They also emphasized that a variation of up to 10% in board density does not significantly affect the board properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated density values of the produced bark particleboards showed a maximum deviation of 5% for both board densities (320 and 420 kg/m 3 ), and the density values were within the tolerance limits specified by TS EN 312. Istek and Siradag (2013) stated that the density of particleboards is influenced by various factors, including raw material and adhesive type, as well as production conditions. They also emphasized that a variation of up to 10% in board density does not significantly affect the board properties.…”
Section: Resultsmentioning
confidence: 99%
“…Wood materials are commonly preferred in construction and engineering due to their aesthetic appearance and ease of workability (İstek and Özlüsoylu 2016;Ergun 2021). However, the increasing population and demands have led to an insufficient supply of solid wood products.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison with previous studies revealed that the IB values of the particleboards with AC were higher than those of some conventional particleboards made from wood or other waste materials. The IB values of particleboards made from wood particles and UF-sodium carboxymethyl cellulose ranged from 0.28 to 0.63 N/mm 2 , depending on the sodium carboxymethyl cellulose concentration [37]. The IB values of particleboards made from bamboo chips with UF ranged from 0.26 to 0.28 N/mm 2 [38].…”
Section: Mechanical Properties Of Particleboardsmentioning
confidence: 98%
“…The modification of UF resins with 5% octadecylamine (ODA)modified bentonite (ODA-BNT) nanoclay showed better adhesion strength and lower free formaldehyde compared with neat UF resins [18]. The effect of sodium carboxymethyl cellulose (Na-CMC) added to UF resin on particleboard production has been investigated and the physico-mechanical properties of particleboard showed the best internal bond (IB) strength in the panels with the 20% Na-CMC admixture [19]. Finely ground birch (Betula verrucosa Ehrh.)…”
Section: Introductionmentioning
confidence: 99%